Severe acute pancreatitis- it’s diagnosis and management- A study of 20 cases - Hossain, Mohammad Monir; Hossain, S M Shakwat; Hossain, Delowar (Community Based Medical Journal, 2019)
Background: Severe acute pancreatitis is defined as pancreatitis in which there is persistent organ failure that does not resolve within 48 hours. Severe acute Pancreatitis is characterized by pancreatic necrosis, a severe systemic inflammatory response and often multiorgan failure. Severe acute pancreatitis is a serious and life threatening disease. Mortality varies from 20 to 50 percent. Objective: The objectives of this study are to develop our knowledge about presentation and diagnosis of severe acute pancreatitis, and to develop a standard management protocol to rescue that patient suffering from severe acute pancreatitis. Methods: This observational study was carried out in Combined Military Hospital (CMH) Dhaka, during the period of August 2014 - Feb 2015. A total 20 patients of severe acute pancreatitis were studied prospectively, evaluated and managed. Results: In this study, out of 20 patients 12(60%) male and 08(40%) female. Male: Female = 3:2. The youngest patient of this series was 03 years and oldest was of 55 years. First categorization of severity of acute pancreatitis was done on the basis of Ranson score. Those patients whose score is 3 or more are categorized as severe. After categorization subsequent management was planned on the basis of laboratory and CT findings. Out of 20 patients all have raised WBC, serum Calcium level decrease in 16 patients, LDH raised in 16 patients, PaO2 decrease in 14 patients, Base deficitincreased in 12 patients, and blood urea nitrate raised in 14 patients. Contrast enhanced CT scan done in all patients and 12 patients were found with reduced enhancement in pancreas, peripancreatic edema and stranding of fatty tissue and remaining 8 patients have fluid collected in peri- and retro pancreatic space. Total 12 patients were given conservative treatment. Remaining 8 patients were operated whose CT findings were reduced enhancement in pancreas and these patients were suspected for infective pancreatic necrosis. In this study 3 patients were expired. Out of these three patients, 2 patients underwent operative intervention and 1 patient was given conservative treatment. Conclusion: Severe acute pancreatitis is a life threatening condition. Its serious regional and systemic involvement causes multiple organ or system failure. Early diagnosis and effective treatment can significantly reduce the mortality and morbidity. CBMJ 2019 July: Vol. 08 No. 02 P: 17-29